O USUFRUTO COMO FATO GERADOR TRIBUTÁRIO: ANÁLISE DA (IN)CONSTITUCIONALIDADE DA INCIDÊNCIA DO IMPOSTO DE TRANSMISSÃO CAUSA MORTIS E DOAÇÃO (ITCMD) SOBRE O USUFRUTO - Lustosa, João Paulo Pessôa Pereira (2024)
How to interpret the usufruct by the Federal Estate Tax (FET)[1]? Based on this problem, this research intended to analyze the (un)constitutionality of the FET on usufruct, as a tax event. The problem comes from the positive normative insufficiency in establishing a clear criterion of materiality for the incidence of the FET, allowing the States and the Federal District to institute indiscriminate tax collection on usufruct as a taxable event, having as a central hypothesis the apparent unconstitutionality of the incidence of ITCMD on civil institute. For this, it was necessary to: (i) literature review on usufruct; (ii) investigation of the limits provided from national regulations to the tax events of the FET ; (iii) analysis of the criterion of (un)constitutionality of the FET on usufruct; (iv) the mapping and cataloging of state and federal district legislation that provided for usufruct as a FET’s taxable event; and (v) presents the results founded. The methodology was mixed - dogmatic and empirical-qualitative. At the end, it was verified that the criterion of the (un)constitutionality of the usufruct as a FET’s taxable event must be verified from the characterization or not of the transfer of assets, having been verified that all federative entities have at least one hypothesis of incidence of the tribute without that there is a need for transfer of assets. [1] Na legislação norte-americana, inexiste um imposto equivalente ao ITCMD do Brasil, de modo que a norma mais próxima ao referido imposto, no sistema normativo norte-americano, é o Federal Estate Tax.